Association between SLCO1B1 rs4149056 and tegafur–uracil-induced hepatic dysfunction in breast cancer. (5th February 2019) - Kamio, Hidenori; Uchiyama, Toshitaka; Kanno, Hitoshi; Onoe, Yoshiko; Saito, Kayoko; Kameoka, Shingo; Kamio, Takako; Okamoto, Takahiro
Aim: The aim of this study was to identify pharmacogenomic biomarkers to predict tegafur–uracil (UFT)-induced liver dysfunction.Patients & methods:  A total of 68 patients, who were administered UFT, were evaluated using a two-step pharmacogenomics analysis.Results: The first screening revealed the association between five SNPs and UFT-induced hepatic dysfunction. In the second step, SLCO1B1 (rs4149056) was found to be the only SNP associated with UFT treatment-related elevation of aspartate aminotransferase (odds ratio: C/C vs T/T = 7.8, C/T vs T/T = 5.7; p = 0.037) and alanine transaminase (odds ratio: C/C vs T/T = 12.2, C/T vs T/T = 4.1; p = 0.034) levels.Conclusion:  The  SLCO1B1 polymorphisms are possible predictors of UFT treatment-related hepatic dysfunction.